German yearbook of international law. - Laun, Rudolf; Mangoldt, Hermann von; Delbrück, Jost (German Yearbook of International Law / Jahrbuch für Internationales Recht., 1994)
Inhaltsverzeichnis Inhalt: K.M. Meessen, Legal Craftsmanship and Political Vision: Wilhelm A. Kewenig's Contributions to the Doctrine of International Law - Sir A. Watts, The International Rule of Law - Y. Dinstein, Some Reflections on Extradition - S. Hobe, Law of Asylum: Solution to the Migration Problem? A Study Concerning Aspects of Public International and European Law with Regard to Aliens and Asylum under Special Consideration of the Law of the European States and the United States of America - M. Kirilova Eriksson, The Legal Position of the Unborn Child in International Law.